Living with Epilepsy: Psychosocial and Clinical Determinants of Quality of Life in Patients with Epilepsy: Psychosocial and Clinical Determinants in Epilepsy - Kazmi, Syed Messum Ali; Chattha, Ali Haider; Afzal, Hasnain; Karim, Rabia; Akhtar, Huma (Pakistan Journal of Health Sciences, 2023)
The present study assessed the role psychosocial (social support, resilience and psychological distress) and clinical determinants (duration of disease and number of seizures per month) in predicting quality of life in epileptic patients. Past research findings have established the role of social support and resilience in impacting psychological distress in quality of life in epileptic patients. Objectives: To evaluate the psychosocial and clinical determinants of quality of life in epileptic patients and to contribute to the gap in the literature. Methods: A quantitative research design was used for the study in which out of 230 progressive patients, 200 were recruited for the study out of which 117 suffered from generalized and 73 suffered from focal epilepsy. In terms of gender differentiation, 110 were male and 90 were females. Kessler Psychological Distress Scale, Brief Resilience Scale and Social Provisions Scale were used. Clinical determinants were assessed through measuring disease duration and number of seizures per month. Data analysis was done using Pearson Product Moment Correlation, MANOVA and Mediation Analysis. Results: Results had shown that there is a significant negative predictive association of psychological distress with quality of life, social support and resilience. However, a significant positive predictive association was identified among psychological distress, duration of disease and number of seizures per month. Conclusion: Significant differences were identified in epileptic patients with regard to psychological distress (high/low) in terms of social support, resilience and quality of life. Social support and resilience significantly mediated the association between psychological distress and quality of life.